Towards 4D cartography: four dimensional dynamic maps for understanding spatio-temporal correlations in lightning events - Resch, Bernd; Hillen, Florian; Reimer, Andreas; Spitzer, Wolfgang (The cartographic journal, 2013)
While graphic variables in 2D maps have been extensively investigated, 4D cartography is still a widely unexplored field. In this paper, we investigate the usefulness of 4D maps (three spatial dimensions plus time) for cartographically illustrating spatio-temporal environmental phenomena. The presented approach focuses mostly on explorative research rather than on enhancement and extension of existing methods and principles. The user study described in the paper shows that 4D cartography is not a well-explored research area and that many experienced map users try to apply their knowledge from 2D maps to 4D dynamic visualisations. Thus, in order to foster the discussion within the community, we formulated several basic research questions for the area of 4D cartography, which range from methods for representing time in 4D visualisations and understanding the temporal context to finding generic methods to achieve optimized temporal generalisation and a consistent definition of graphical variables for 3D and 4D.
Gesehen am 03.01.2022